La Hallyu como medio configurante entre el sistema familiar y el sujeto perteneciente a ella (2023)
Hallyu is a cultural movement that is expanding at great speed and is reaching the homes of each country in a globalized way. Therefore, this research addressed the relationship between three young people who are part of Hallyu and their family, taking into account this new culture that is entering their family. In this research, the configuration of the family dynamics of the subject belonging to Hallyu was analyzed, through a qualitative approach research, conducting interviews with 3 young people from the city of Bogotá.